Organization and Management of a Business Enterprise (Book). - Elwell, F. H. (The Accounting Review, 1936)
Reviews the book "Organization and Management of a Business Enterprise," by Karl D. Ferstrom, Robert F. Elder, Wyman P. Fiske, Albert A. Schaefer and B. Alden Thresher.